2011
DOI: 10.1590/s1808-86942011000500021
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cross-cultural adaptation and validation of SinoNasal Outcome Test (SNOT): 22 to Brazilian Portuguese

Abstract: Qual ity of life questionnaires have been increasingly used in clinical trials to help establish the impact of medical intervention or to assess the outcome of health care services. Among diseasespecific outcome measures, SNOT-22 was considered the most suitable tool for assessing chronic rhinosinusitis and patients with nasal polyps. Aims:To perform translation, cross-cultural adaptation and validation of the SNOT-22 to Brazilian Portuguese. Methods:Prospective study involving eighty-nine patients with chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
4
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 11 publications
(30 reference statements)
6
120
4
6
Order By: Relevance
“…The SNOT-22 index (difference between values from before and after the treatment) of the patients decreased, on average, 20.3 points. Nineteen patients (57.6%) exhibited a decrease of >14 points, which was considered significant 9 (Table 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNOT-22 index (difference between values from before and after the treatment) of the patients decreased, on average, 20.3 points. Nineteen patients (57.6%) exhibited a decrease of >14 points, which was considered significant 9 (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…The normality limit for the Brazilian SNOT-22 is 10 points, and a variation of >14 points among the SNOT-22 indexes of the same patient is considered significant. 9 The patients completed the SNOT-22 questionnaire before the beginning of the treatment and when they returned after 8 weeks of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…This means that the studied subjects may have had a better socioeconomic status than the patients of the studies of Kosugi et al 8 and Mascarenhas et al 13 whose subjects used a public health service.…”
Section: Discussionmentioning
confidence: 97%
“…Soler et al 8 conducted a study with 242 patients analysed over time and found that patients selected for the surgical treatment obtained worse SNOT-22 scores than patients who chose clinical treatment. Factors such as demographic characteristics, patient-doctor relationship, comorbidities and personality did not influence the surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Untuk menilai kondisi hidung pasien dilakukan dengan metode LundKennedy. 1,12 Analisis statistik dilakukan menggunakan SPSS 15.0 for windows. Pemakluman (informed consent) didapat dari semua partisipan yang masuk kriteria inklusi pada studi ini.…”
Section: 8unclassified